The medium is the message probing photography's capacity to influence people's understanding of reality - Villanueva, Julius Voltaire S.
The medium is the message probing photography?s capacity to influence people?s understanding of reality, looks at how Media Ecology works within the field of Photography. It probes into the capability of the photograph to either reflect or alter people?s view of reality. By examining, consolidating, and integrating ideas about the very nature of photography, this study engaged in producing photographs that serve as probes on how alteration of reality can be achieved. This research production made use of the different photographic principles and various techniques of manipulation done through image-editing softwares, such as Adobe Photoshop and iPhoto, to see whether it can really alter people?s reality. It was found that changing the visual aspects of the photograph can affect the viewers? way of looking at the photo, and thus, influence their perception. Manipulation paved the way for the reality of the viewer to be altered. And since people readily believe in photographs, they tend to accept what is being shown, and thus, it becomes their reality. Given these findings, it can be said that photography has the capacity to alter people?s reality. It is a reality that humans make meanings about, and this includes how a photograph is composed. It is a social construction that changes depending on the cultural background, religious orientation, beliefs, and the upbringing of both the photographer and the viewer. It is the way people experience the world, that is, a meaning-making process. And since the photograph can be altered, so is reality.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media arts